PENGARUH PEMIKIRAN IBNU MADHAâ€™ TENTANG USHUL AL-NAHWI AL-â€˜ARABI DALAM MEMAHAMI TEKS KEAGAMAAN - Faisol, M. (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
â€Nahwuâ€ or sintax is a science born in the era of codification (Ashr al-Tadwin). In this field, there are many schools: Kufa, Bashrah, Baghdad, Egypt and Andalus. Each school has its own method and thought or what is called ushul al-nahwi (qiyas, taâ€™lil, taâ€™wil and amil). This research in included in the study of thought. The public figure of this research object is Ibnu Madhaâ€™, that is his ideas on ushul al-nahwi al-arabi and the implication in understanding divine texts. Ibnu Madhaâ€™ refused the concept of ushul al-nahwi al-arabi: qiyas, amil, taâ€™lil dan taâ€™wil, that have beeen made as the concept of mental interpretatif (al-Shurah al-Zhihniyyah al-Taâ€™wiliyyah) in lying the foundation of Arabic language. Ibnu Madhaâ€™ refusal to the ushul al-nahwi opens up the space of freedom for reason to express in order to obtain the meaning that is not stated literally in the text.